Refugia flowers enhance insect pollinator and quality of fruit production in strawberry farming - SAKINAH AMANINA; NINA MARYANA; I WAYAN WINASA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Amanina S, Maryana N, Winasa IW. 2025. Refugia flowers enhance insect pollinator and quality of fruit production in strawberry farming. Biodiversitas 26: 1310-1316. Strawberry flowers have different receptive and anthesis periods, making them generally cross-pollinated. Adding refugia flowers in strawberry farming can attract more insect pollinators, enhancing successful cross-pollination and complete fruit formation. This research aimed to study the effect of refugia flowers in improving the diversity and abundance of insect pollinators and, eventually, fruit production and quality in strawberry farming. The research was conducted in Sukaresmi Village, Rancabali Sub-district, Bandung District, West Java, Indonesia using a randomized group experimental design consisted of four treatments, namely strawberries plants without refugia (control/C), strawberries and common zinnia (Zinnia elegans) (SZ), strawberries and marigold flowers (Tagetes sp.) (SM) and strawberries and cosmos flowers (Cosmos sp.) (SC). Observations of pollinators were conducted at 06.00-09.00, 10.00-13.00, and 14.00-17.00 every three days for 30 days. Data was subjected to analysis of diversity and abundance, Analysis of Variance (ANOVA), Chi-Square test, and correlation analysis. The highest pollinator diversity was found in the SC treatment, and the lowest was in the control, although the diversity level in all treatments was moderate. The cosmos flowers also attracted the most significant number of individual pollinators. Three dominant pollinators were found in all plots, i.e. Apis cerana, Melanostoma sp., and Episyrphus viridaureus. Furthermore, the abundance of pollinators affected the quantity of perfect fruit and quality of strawberry fruits, with SC treatment producing the highest fruit yield and quality on average. The findings of this study imply that adding cosmos flowers positively impacts pollinators, which helps produce better strawberries.